LC–MS/MS Analysis of Choline Compounds in Japanese-Cultivated Vegetables and Fruits - Wenhao Wang; Shohei Yamaguchi; Masahiro Koyama; Su Tian; Aya Ino; Koji Miyatake; Kozo Nakamura (Foods, 2020)
Choline is an essential nutrient and choline esters are potential functional food ingredients. We aimed to analyze the choline compound content in 19 cultivated fruits and vegetables and identify those with high acetylcholine content. We utilized liquid chromatography with tandem mass spectrometry to quantify choline compounds according to the standard addition method. Choline compounds were extracted from lyophilized fruit/vegetable powders and passed through a weakly acidic cation exchange column, resulting in a concentrated solution of choline compounds. The compounds were separated on a pentafluorophenyl column and then analyzed using positive mode electrospray ionization. Results showed that acetylcholine and choline were the primary choline compounds in all agricultural products; propionylcholine and butyrylcholine were minor compounds in 17 and 12 agricultural products, respectively. The acetylcholine concentration was 2900-fold higher in eggplants (6.12 mg/100 g fresh weight [FW]) than in other agricultural products (average: 2.11 × 10−3 mg/100 g FW). The concentration of acetylcholine differed only 2-fold between eggplant cultivars with the highest (′Higomurasaki′: 5.53 mg/100 g FW) and lowest (′Onaga nasu′: 2.79 mg/100 g FW) concentrations. The half-life of acetylcholine in eggplants was approximately 16 days, which is longer the shelf life of eggplants. Thus, eggplants can be a good source of acetylcholine.